2011
DOI: 10.2478/v10086-011-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Lake minnow, Eupallasella percnurus (Pall.), in Kujawsko-Pomorskie Voivodeship in Poland - past and present occurrence and protection

Abstract: Abstract. Knowledge of the historical occurrence of the endangered cyprinid fish species, Eupallasella percnurus (Pall.), in today's Kujawsko-Pomorskie Voivodeship in Poland is sparse. However, a total of nine sites inhabited by this species had been identified by the end of the twentieth century, but only one of theses had survived into the early 2000s. The largest field inventory to date of this area was undertaken from 2005 to 2011 and nine new sites were recorded. Most of the newly discovered sites inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Other regions, however, seem to have less endangered sites in comparison to Eastern Poland. Sikorska and Wolnicki (2011) indicated only one site in the Wielkopolskie voivodeship, and Wolnicki et al (2011c) found two sites in the Kujawsko-Pomorskie voivodeship classified as critically threatened. Generally, at least 75% of habitats of lake minnow are currently in danger of being destroyed (Kaczmarczyk and Wolnicki 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other regions, however, seem to have less endangered sites in comparison to Eastern Poland. Sikorska and Wolnicki (2011) indicated only one site in the Wielkopolskie voivodeship, and Wolnicki et al (2011c) found two sites in the Kujawsko-Pomorskie voivodeship classified as critically threatened. Generally, at least 75% of habitats of lake minnow are currently in danger of being destroyed (Kaczmarczyk and Wolnicki 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, there are about 160 sites distributed non-uniformly in five voivodeships: Pomorskie, Wielkopolskie, Kujawsko-Pomorskie, Mazowieckie, and Lubelskie (Radke et al 2011, Sikorska et al 2011, Wolnicki et al 2011a, b, c). The vast majority of the sites are found in the Pomorskie Voivodeship and in the Lubelskie Voivodeship (Wolnicki et al 2011a).…”
Section: Study Sitementioning
confidence: 99%
“…It is known that several populations of E . percnurus have disappeared in Poland over recent decades (Wolnicki et al , ). Future research should be aimed at investigating to what extent environmental conditions disturb male reproduction and contribute to the extinction of local E .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 165 sites known in Poland, over 120 are under threats of anthropogenic or natural origin, in particular swamp draining, amelioration, deforestation and infilling. Most of the historic sites have disappeared over the last two decades (Wolnicki et al , ). Eupallasella percnurus is included among the animal species with the highest priority in the Natura 2000 European Ecological Network, in the group of species that requires active protection measures (Radtke et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, almost 50% of the sites in this region are considered to be threatened to low degree (Table 1). In other voivodeships the share of such sites is generally lower (Wolnicki and Radtke 2009, 2010, Radtke et al 2011, Wolnicki et al 2011a, 2011b.…”
Section: Threatsmentioning
confidence: 99%